Pengaruh literasi keuangan terhadap kinerja umkm di Surabaya - Anjar Faishal Amri; Iramani Iramani (Journal of Business & Banking, 2018)
MSME is a form of business in Indonesia. This large number of businesses has a high influence on Indonesia. The main purpose was to determine the relationship between financial literacy on MSME performance in Surabaya City. The study was used 73 data MSME owners in Surabaya City. Cluster and purposive sampling techniques were used to select a sample. The data were collected using structured questionnaires. Validity and reliability techniques were also used to test the consistency of the indicators and analytical techniques. Descriptive statistics was used to analyze the data, and data were presented in the form of tables, fi gures, and percentages. Inferential statistics was also used to test hypotesis. The fi ndings are indicative of a signifi cant effect of bookkeeping literacy, debt literacy, and budgeting literacy on MSME performance. It is recommended that MSME owner to improve the ability make and manage cash management.